2021
DOI: 10.3390/v14010029
|View full text |Cite
|
Sign up to set email alerts
|

Complement Inhibitors Vitronectin and Clusterin Are Recruited from Human Serum to the Surface of Coronavirus OC43-Infected Lung Cells through Antibody-Dependent Mechanisms

Abstract: Little is known about the role of complement (C’) in infections with highly prevalent circulating human coronaviruses such as OC43, a group of viruses of major public health concern. Treatment of OC43-infected human lung cells with human serum resulted in C3 deposition on their surfaces and generation of C5a, indicating robust C’ activation. Real-time cell viability assays showed that in vitro C’-mediated lysis of OC43 infected cells requires C3, C5 and C6 but not C7, and was substantially delayed as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Recently, a chaperone, APOJ (as clusterin), has been suggested to be involved in several basic biological events such as the maintenance of protein homeostasis imbalance-induced cell death, cancer progression, and neurodegenerative disorders; 27 , 28 meanwhile it was verified to serve as a complement cascade inhibitor in a variety of conditions. 29 Hence, to investigate whether APOJ is involved in the effect of HSF1 on PD-L1 expression, we performed a APOJ knockdown followed by HSF1 overexpression in HCC cells and found that after APOJ knockdown, HSF1 overexpression did not significantly upregulate the expression of PD-L1 in HCC cells ( Figure 2a-b ). The result suggested that HSF1-induced PD-L1 expression mentioned above depended on the existence of APOJ in HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a chaperone, APOJ (as clusterin), has been suggested to be involved in several basic biological events such as the maintenance of protein homeostasis imbalance-induced cell death, cancer progression, and neurodegenerative disorders; 27 , 28 meanwhile it was verified to serve as a complement cascade inhibitor in a variety of conditions. 29 Hence, to investigate whether APOJ is involved in the effect of HSF1 on PD-L1 expression, we performed a APOJ knockdown followed by HSF1 overexpression in HCC cells and found that after APOJ knockdown, HSF1 overexpression did not significantly upregulate the expression of PD-L1 in HCC cells ( Figure 2a-b ). The result suggested that HSF1-induced PD-L1 expression mentioned above depended on the existence of APOJ in HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that VTN , together with other proteins involved in the extracellular matrix organization, were highlighted as belonging to a cluster of molecules that are significantly upregulated only in COVID-19 patients with fatal pneumonia compared to those with severe pneumonia requiring ICU admission, and to subjects with pneumonia that do not require ICU admission [ 4 ]. Interestingly, this protein has been also reported to be recruited together with Clusterin by coronavirus-infected cells from human serum through Antibody-Dependent Mechanisms, and to be associated with delayed Complement-mediated death, provoking a series of implications related to viral pathogenesis and tissue tropism [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the complement inhibitors, clusterin and CD59 were upregulated in the monocytes and neutrophils from the CAPM cohort. Thus, it is possible that viruses and fungi can downplay complement activation by inhibiting MAC assembly 50,51 . Coagulation is an early protective response and can be detrimental if it leads to thrombotic or haemorrhagic coagulopathy 52–54 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that viruses and fungi can downplay complement activation by inhibiting MAC assembly. 50,51 Coagulation is an early protective response and can be detrimental if it leads to thrombotic or haemorrhagic coagulopathy. [52][53][54] The gene sets in…”
Section: Immunological Pathwaysmentioning
confidence: 99%